Réponses

2012-11-11T15:34:00+01:00

(-2x+1)(x+4)=3(4x-2)(x+1)

-(2x-1)(x+4)-3(4x-2)(x+1) = 0

-(2x-1)(x+4)-6(2x-1)(x+1) = 0

(2x-1)(x+4)+6(2x-1)(x+1) = 0

(2x-1)(x+4+6x+6) = 0

(2x-1)(7x+10) = 0

 

2 solutions :

x = 1/2

ou

x = -10/7

 

f(20) = -125/3 et f(-17)=134/3

 

y = ax + b

 

-125/3 = 20a + b

134/3 = -17a + b

 

-125/3 - 134/3 = 20a + 17a

  259/3 = 37a

a = 259/111

 

b = 134/3 - 17*259/111

b = 134*111/333 - 4403*3/333

b = (14874 -  13209)/333

b = 1665/333

 

donc f(x) = 259x/111 + 1665/333

 

En espérant t'avoir aidé.

2012-11-11T16:21:10+01:00

(-2x+1)(x+4)=3(4x-2)(x+1)

-(2x-1)(x+4)-3(4x-2)(x+1) = 0

-(2x-1)(x+4)-6(2x-1)(x+1) = 0

(2x-1)(x+4)+6(2x-1)(x+1) = 0

(2x-1)(x+4+6x+6) = 0

(2x-1)(7x+10) = 0

 

2 solutions :

x = 1/2

ou

x = -10/7

  aprés je sais pas :/